FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT PENGETAHUAN REMAJA PUTRI TENTANG DISMINOREA - Mulyana, Desi Nurlaela; Indriyani, Devia (Universitas Malahayati Bandar Lampung, 2021)
Dysmenorrhea is a symptomatic phenomenon that includes abdominal pain, cramps, and back pain. Gastrointestinal symptoms such as nausea and diarrhea may occur as a symptom of menstruation. The purpose of this study was to determine the factors associated with the level of knowledge of young women about dysmenorrhea in RT 001, Kp. Tambun Kapling, Setia Pahlawan Village, Tarumajaya District, Bekasi Regency in 2020.The research is descriptive quantitative analysis, the sample in this study were 38 young women, data collection by distributing questionnaires and analyzed using Chi Square test.From the results of the research, there were 15 girls (39.5%) with good knowledge, 23 people (60.5%). And among the variables of menarche age at >12 years (57.9%) <12 years 16 (42.1%), sources of information through electronic media 22 (57.9%) non-electronic media 16 (42.1%), the role of parents are quite 27 (71.1%) good 11 (28.9%), and the nutritional status of thin 9 (23.7%) normal 29 (76.3%) .The results of the analysis of this study showed that there was no relationship between age, source of information and nutritional status with knowledge, but there was a relationship between the role of parents and the knowledge of adolescent girls about dysmenorrhea, from the analysis results obtained OR = 2.1 (95% CI: 0.463- 9,839) adolescents with